Is Islamic architecture synonymous with mosque architecture? - Spahic, Omer (IIUM Press, 2021)
This article discusses the meaning and significance of Islamic architecture. It adds a new dimension to the subject by addressing it from the perspective of the genesis and evolution of the mosque institution and its architecture. The article concludes that mosque architecture functioned as the quintessence and also driving power of Islamic architecture. However, it is not to be fully identifiable with it. Despite a great many similarities, there were many aspects of Islamic architecture that evolved on their own and functioned independently from the vocabulary of mosque architecture. There were yet others which, even though originating within the orb of mosque architecture, assumed supplementary imports and functions elsewhere. The topic in question is viewed through the prism of the mosque institution as the basis of all other institutions, and of the institutional ideological harmony in Islamic civilization through which the mosque institution served as an incubator of general architectural creativity.